Unveiling the Impact Skilled Migration has on the Creative Class: Panel Data Analysis for EU Countries - Uctu, Ramazan; Koç, Şerife; Mercan, Birol (Ekonomika, 2025)
Innovation and creativity lie at the heart of countries’ ability to grow and improve the living standards of their people. Specifically, innovative and creative individuals contribute to economic growth as they bring with them ideas that will produce new knowledge and new technologies. As such, countries have attempted to develop policies that will attract such individuals in order to facilitate and accelerate the growth process. This article examines the theoretical foundations of the creative class, their economic impact and investigates the role of skilled migrants in shaping the creative economy by using data for 22 European Union countries during the period 2007–2021. The study uses the dynamic panel data model with Arellano and Bover/Blundell and Bond System Generalized Moments (One Step SGMM and Two Step SGMM) estimators. The results demonstrate that skilled immigration, research and development expenditures and the exportation of high-tech products have a positive effect on a skilled labor force.
Keywords: The Creative Class Theory; Creativity Index,; Skilled migration,; selected EU countries